Systematic C‐reactive protein monitoring reduces hospital stay after laparoscopic ileal pouch–anal anastomosis. A comparative study of 158 consecutive patients with ulcerative colitis. (18th July 2022) - de Ponthaud, Charles; Guyard, Clémence; Blondeau, Marc; Giacca, Massimo; Monsinjon, Marie; Frontali, Alice; Panis, Yves
Abstract: Aim: C‐reactive protein (CRP) is a common biomarker of inflammation which has largely been used to predict the risk of postoperative septic complications after colorectal surgery. However, no data exist concerning its potential benefit after ileal pouch–anal anastomosis (IPAA) for ulcerative colitis (UC). The aim of this study was to evaluate a CRP‐driven monitoring discharge strategy after laparoscopic IPAA for UC. Methods: Since 2012, 158 patients undergoing a laparoscopic IPAA for UC have been included: 66 patients (CRP group) operated since 2016 had a CRP‐driven monitoring discharge on postoperative day 5 (POD 5) and were discharged on POD 6 if CRP < 100 mg/L; these patients were matched (according to age, gender, body mass index, IPAA in two or three steps) to 92 patients operated between 2012 and 2016 without any CRP monitoring (control group). Results: Median length of hospital stay was shorter in the CRP than the control group (7 vs. 9 days; P < 0.001) and discharge on POD 6 occurred more frequently in the CRP group (47% vs. 7%, P < 0.001). No difference was observed between the two groups concerning overall morbidity ( P = 0.980), surgical site infection ( P = 0.554), Clavien–Dindo ≥ IIIa morbidity ( P = 0.523), unplanned rehospitalization ( P = 0.734) and 30‐day reoperation ( P = 0.240). Conclusion: CRP‐driven monitoring discharge strategy after laparoscopic IPAA for UC is associated with a significant reduction in length of hospital stay, without increasing morbidity, reoperation or rehospitalization rates.